Let's evaluate each statement to determine which one is not true.
A. \(8 + 7 = 7 + 8\)
This is true because of the commutative property of addition.
B. \(8 = 12 - 4\)
This is true because \(12 - 4\) equals \(8\).
C. \(11 + 4 = 7 + 8\)
Calculating both sides:
\(11 + 4 = 15\)
\(7 + 8 = 15\)
This is true.
D. \(8 = 7 = 13 - 2\)
This is ambiguous because it attempts to assert equality among three terms. The correct interpretation would be \(8 = 7\) (which is false) and \(7 = 13 - 2\) (which is true, as \(13 - 2\) equals \(11\)). Therefore, not all parts of this equation hold true.
So, the statement that is not true is D.